Analysing Grief on Twitter: A Study of Digital Expressions on Om Puri’s Death - Rajan, Benson; Sarkar, Sahana (Funes. Journal of narratives and social sciences, 2018)
Digital media, particularly social media, have changed the way we interact and communicate. New media technologies have expanded our connections with people on a global scale (Williams, 2007). Today we can communication with celebrities with ease. One of the ways to achieve this is through following them on social media; here one can interact with the celebrities posts and comments online (Sanderson, Cheong, 2010). This sense of attachment makes the mourning of celebrity deaths consequential in creating ‘communities for mourning’ (Gibson, 2007). It also sustains and extracts global attention. Hence, online platforms are increasingly influencing the way we grieve both in the case of personal loss and in mourning a celebrity death. Grief is the most ubiquitous painful experience. With the advent of the Internet, online expressions of grief have increased considerably. The sensation surrounding the death of celebrities has increased in the online space post 2008. Om Puri1 passed away on 6 January 2017. His unexpected death was at the centre of many discussions because of its untimely nature as well as a suspicious bruise that appeared on his head. The reports and various speculations surrounding his death were widely discussed on Twitter by news websites, blogs and other Twitter users. Through this optic, this study aims to explore the different categories of mourning messages about Om Puri’s death on Twitter and to understand if social mourning mirrors the traditional eulogy. An inductive approach of qualitative content analysis is used to analyse the tweets in response to Om Puri’s death.